PENGARUH KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, TINGKAT HUTANG, DAN ARUS KAS OPERASI TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Sub Sektor Otomotif yang terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Retno Fuji Oktaviani; Rinny Meidiyustiani (Jurnal Ilmiah Ekonomi Bisnis, 2021)
Earnings Persistence is one component of earnings quality. This study aims to know the effect of managerial ownership, firm size, debt level, and operating cash flow on earnings persistence. The population in this study was the automotive sub-sector manufacturing company listed on the Indonesia Stock Exchange from 2013 to 2017. The sample selection technique used purposive sampling and obtained 8 companies included in the 5-years period so that 40 samples were observed. The method of data analysis in this study is multiple linear regression analysis using SPSS v20.0. The result of this study indicate that only the level of debt has a significant effect on earnings persistence. While managerial ownership, firm size, and operating cash flow have no significant effect on earnings persistence.